A Review Of The Many Cost Approach Methods For Minerals Valuation - T. R. Ellis (Society for Mining, Metallurgy & Exploration, 2011)
Many appraisers/valuers believe that the only valuation method available within the Cost Approach category for Real Property appraisal is the depreciated replacement cost method. Some valuation and financial reporting standards setters also believe the same. This paper introduces the minerals appraiser to a number of useful methods for mineral property appraisal that are based primarily on the principle of contribution to value, the predominant economic principle in the cost approach. Most of these cost approach methods discussed are primarily for use in valuation of exploration tracts and resource properties that have no defined reserves. However, the powerful rural cost method can be used to calculate the contribution of categories of resources, reserves, and other property components to the value of a mineral property. This method can be applied to mineral properties at all stages of development, including producing properties.